2019
DOI: 10.3390/ijms20112772
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Mutation Affects Clock Gene-Dependent Energy Metabolism

Abstract: Growing evidence highlights a tight connection between circadian rhythms, molecular clockworks, and mitochondrial function. In particular, mitochondrial quality control and bioenergetics have been proven to undergo circadian oscillations driven by core clock genes. Parkinson’s disease (PD) is a chronic neurodegenerative disease characterized by a selective loss of dopaminergic neurons. Almost half of the autosomal recessive forms of juvenile parkinsonism have been associated with mutations in the PARK2 gene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…For example, the PRKN mutation may influence crosstalk between the TTFL and mitochondrial bioenergetic pathways. Fibroblasts taken from two genetic PD patients exhibited dampened oscillations in bioenergetic activities, reduced rates of mitochondrial oxygen consumption, and dysregulated TTFL factor expression patterns - CLOCK, CRY1, and CRY2 were upregulated while PER2 was downregulated in these cells ( Pacelli et al, 2019 ). Epigenetic modifications may also play a role in aberrant clock gene expressions.…”
Section: α-Synuclein Proteinopathiesmentioning
confidence: 99%
“…For example, the PRKN mutation may influence crosstalk between the TTFL and mitochondrial bioenergetic pathways. Fibroblasts taken from two genetic PD patients exhibited dampened oscillations in bioenergetic activities, reduced rates of mitochondrial oxygen consumption, and dysregulated TTFL factor expression patterns - CLOCK, CRY1, and CRY2 were upregulated while PER2 was downregulated in these cells ( Pacelli et al, 2019 ). Epigenetic modifications may also play a role in aberrant clock gene expressions.…”
Section: α-Synuclein Proteinopathiesmentioning
confidence: 99%
“…Along with this line of evidence, we showed in earlier studies that primary parkinmutant fibroblasts, carrying different mutations in the PARK2 gene, displayed severe ultrastructural abnormalities, mainly in mitochondria [4,24], altered expression of proteins involved in structural dynamics of cytoskeleton, oxidative stress response, Ca 2+ homeostasis, and RNA processing [25,26]. Furthermore, parkin-mutant fibroblasts showed an altered lipid profile [27], dysfunctions of lysosomal function [28] and of clock gene-dependent energy metabolism [29], and higher Ca 2+ and cAMP basal levels [4,5,30].…”
Section: Introductionmentioning
confidence: 53%
“…For instance the regulation of endoplasmic reticulum-to-mitochondrial contacts by Parkin via Mfn-2 (Basso et al, 2018). Also, Pacelli et al (2019) reported altered severe damping of the bioenergetic oscillatory patterns associated to circadian rhythms and molecular clockworks in fibroblasts from PRKN-PD patients that may conditioning mitochondrial quality control and mitophagy. One study performing a whole-genome expression analysis by RNA-sequencing found that different PRKN mutations were associated with a large number of gene expression changes at the transcriptome level (González-Casacuberta et al, 2018).…”
Section: Molecular Mechanisms Underlying Pd Pathogenesis: Mitochondrimentioning
confidence: 98%